2019
DOI: 10.1155/2019/9726786
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Gut Microbiota of Viral Hepatitis Cirrhosis

Abstract: Although gut dysbiosis appears in 20%–75% of cirrhotic patients, there are limited data on microbiota profiles in viral hepatitis cirrhotics and its role in progression to cirrhosis. Further understanding on the relationship between gut dysbiosis and cirrhosis presents a unique opportunity in not only predicting the development of cirrhosis but also discovering new therapies. Recent advances have been made on identifying unique microbiota in viral hepatitis cirrhotics and adopting the microbiota index to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…TLR3 also plays a pivotal role in liver brosis. The gut microbiota can stimulate liver immunity, effectively helping in the immune response to a hepatitis virus [29]. Studies have indicated a relationship between microbial composition and chronic liver disease or cirrhosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 also plays a pivotal role in liver brosis. The gut microbiota can stimulate liver immunity, effectively helping in the immune response to a hepatitis virus [29]. Studies have indicated a relationship between microbial composition and chronic liver disease or cirrhosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…These inherent characteristics could be applied in vaccine development. Furthermore, the adjuvanticity of probiotics [ 109 , 135 , 181 ] could be applied in vaccine development of SARS-CoV2 [ 89 ]. Above all, the efficiency of nasal immunizations with some recombinant LAB particularly over respiratory pathogens such as tuberculosis, coronavirus, influenza, and respiratory syncytial virus has been reported [ 182 186 ].…”
Section: Probiotics the Best Alternative As Mucosal Vaccine Vectorsmentioning
confidence: 99%
“…Although the shift and function of gut microbiota in response to viral pathogens remains poorly studied, the literature available for the moment indicates marked changes in gut microbiota composition in association with immune activation and chronic inflammation, as is the case for HIV ( 9 ), hepatitis B virus ( 228 ), HCV ( 107 ), and rotavirus ( 73 ). Consequently, the viral replication is accompanied by defects in epithelial barrier integrity and immune homeostasis, leading to microbial translocation that, in turn, contributes to immune activation, inflammation, and disease progression.…”
Section: Polyphenols and Modification Of Respiratory And Intestinal Mmentioning
confidence: 99%